1999
DOI: 10.1002/hrdq.3920100403
|View full text |Cite
|
Sign up to set email alerts
|

The effect of gender role, attitude toward leadership, and self‐confidence on leader emergence: Implications for leadership development

Abstract: Although research has indicated no substantial differences between the behaviors of male and female leaders, differences exist in perceptions of these behaviors. Leadership continues to be described in stereotypically masculine terms, although some evidence exists that an androgynous leadership style also may be related to perceptions of leadership. This study examined whether self‐perceptions of masculine gender role characteristics would predict individuals who were perceived by others as leaders on a team p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
89
1
3

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(101 citation statements)
references
References 42 publications
5
89
1
3
Order By: Relevance
“…Self-report measures have been shown to be a reliable way of measuring leader self-perception, with several studies demonstrating their predictive validity. (Kolb, 1999).…”
Section: Co-evolution Of Leadership and Self-view As A Leadermentioning
confidence: 99%
“…Self-report measures have been shown to be a reliable way of measuring leader self-perception, with several studies demonstrating their predictive validity. (Kolb, 1999).…”
Section: Co-evolution Of Leadership and Self-view As A Leadermentioning
confidence: 99%
“…They found that when female subjects were asked to describe characteristics of effective male and effective female leaders, female leaders were rated higher in consideration and structure. Couple this finding with the assertion that female leaders may be in a "double-bind" when exhibiting stereotypical masculine (leadership) behaviors (Kolb, 1999). In addition, she cites several studies that find that emulation of masculine leadership behaviors by women can have a negative effect on evaluation of them as leaders.…”
Section: Social Role Theory Gender Stereotypesmentioning
confidence: 81%
“…Given the contextual nature of masculinity, it is proposed that in this particular sample, participants phrased their occupation through traditionally masculine signifiers, such as toughness and strength, as affirmed by participant conceptualisations of masculinity and past research (Boyce and Herd 2003;Kolb 1999). As conventional signifiers of masculinity, toughness and endurance are within the framework of hegemonic masculinity.…”
Section: Endurancementioning
confidence: 97%
“…These discourses of masculinity were related to traditionally masculine signifiers, such as strength and dominance (Boyce and Herd 2003;Kolb 1999). By aligning masculinity to hegemonic norms, escorts defined their occupations by a framework that dominated and subordinated them.…”
Section: Conceptualisations Of Masculinity Within the Samplementioning
confidence: 99%